Consensus of Continuous-Time Multiagent Systems with General Linear Dynamics and Nonuniform Sampling. (11th June 2013) - Gao, Yanping; Liu, Bo; Zuo, Min; Jiang, Tongqiang; Yu, Junyan
Abstract : This paper studies the consensus problem of multiple agents with general linear continuous-time dynamics. It is assumed that the information transmission among agents is intermittent; namely, each agent can only obtain the information of other agents at some discrete times, where the discrete time intervals may not be equal. Some sufficient conditions for consensus in the cases of state feedback and static output feedback are established, and it is shown that if the controller gain and the upper bound of discrete time intervals satisfy certain linear matrix inequality, then consensus can be reached. Simulations are performed to validate the theoretical results.